THE ANALYTICAL SOLUTION TO UNSTEADY FLOW OF DUSTY BINGHAM FLUID BETWEEN TWO PARALLEL RIGA PLATES WITH RADIATION EFFECTS - Lawal, Olwafemi Waheed; Soliu, Q. Damilola; Sikiru, A. Babatunde (FUDMA JOURNAL OF SCIENCES, 2024)
The study at hand is to delve into the analytical solution for the unsteady flow of dusty Bingham fluid between two parallel Riga plates with radiation effect. The plates, which includes the upper Riga plate and lower Riga plates are assumed to be immovable hence stationary. The velocity of the fluid is assumed to be identical as that of the velocity of the particle (dusty fluid). The governing equations for the problem is been modeled as dimensionless non-homogeneous PDE (partial differential equation) with non-homogeneous boundary condition. The equations are then solved analytically with the method of Eigenfunction expansion. The impacts of numerous relevant parameters for the velocity and temperature field are scrutinized in details with the use of graphs. Furthermore, graphical explanations are provided on the factors of the friction and the influence of the above parameters on the pattern of the flow together with the shear stress and Nusselt number. Finally, both quantitative and qualitative comparisons are presented.
Keywords: Riga plates; Bingham dusty fluid; Non-homogeneous partial differential equation; Analytical method; Radiation effect; Eigenfunction expansion